Information systems and their contribution to Venezuelan educational institutions (Innovaciones Educativas, 2023)
This research's main objective was to determine the contributions of the information system "Educa," designed by the company "Internacional de Sistemas Empresariales" for the administration and academic management of the educational institutions in Maracaibo, Zulia State, Venezuela. In addition, the proposal evaluates the system's usage frequency to diagnose the institutions' technological skills and establish their efficiency for decision-making, planning, and communication procedures. The methodological proposal was adopted under an interpretive paradigm, built under a qualitative approach with a temporary transversal scope. The data collection was established through a semi-structured interview, with the support of a simple selection survey, applied to the system's users in four educational institutions that served as a sample among a population of twenty-six institutions. The subjects of information were the users of the departments of the study control, administration, and teachers in the area of ​​primary and high school. Among the findings, it was determined that the users of the Educa system can identify opportunities and/or threats more easily; based on this, they can establish guidelines that serve to set the direction in immediate or future decisions of the institution that lead them to the fulfillment of their objectives. Likewise, a relationship was established between planning, decision-making, and the communication process with the Educa system, thus reducing errors in the scheduled academic and administrative tasks.
Keywords: management information system; educational management; planning; communication; decision making; problem solving